Stakeholder consultation workshop on leveraging digital solutions in agricultural extension: Pathways to inclusive and sustainable farming - Gakhar, Shalini; Singaraju, Niyati; Bharti, Preeti; Patwar, Shelly; Nagaraji, Satish; Kiragi, Pratibha; Maria, Sherin (CGIAR Research Initiative on Digital Innovation, 2024)
The Stakeholder Consultation Workshop on Leveraging Digital Solutions in Agricultural Extension: Pathways to Inclusive and Sustainable Farming was co-organized by the International Rice Research Institute (IRRI) and the International Maize and Wheat Improvement Center (CIMMYT) on November 29 and 30, 2024, at Mayfair Lagoon, Bhubaneswar, Odisha. The workshop was part of CGIAR’s Digital Innovation initiative, which aims to coordinate digital research across various research centers and institutions to foster collaboration, synergy, and an inclusive, holistic, and impactful approach to agricultural digital innovation. Agricultural extension plays a crucial role in equipping farmers with practical knowledge, technologies, and techniques to enhance productivity and sustainability. Emerging digital technologies, such as artificial intelligence (AI), are rapidly evolving and providing farmers with personalized, real-time insights and predictive analytics to improve efficiency, resource management, and climate resilience. Governments, international organizations, and the private sector are increasingly focused on harnessing AI and other digital innovations to create inclusive, efficient, and sustainable agricultural extension systems.